The Development of E-Commerce and Its Impact on Changes in Consumption Patterns and Behavior of Indonesian People in The Digital Economy Era: A Literature Study In 2020–2025 - Sriwanti Belani; Rini Hadiyati (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
E-commerce has become one of the main drivers of digital economic growth in Indonesia. The expansion of internet access, the use of smartphones, and rapid digital payment systems have accelerated the adoption of online transactions and changed consumer behavior. This research aims to analyze the development of e-commerce in Indonesia and examine its impact on changes in consumption patterns and consumer behavior during the 2020-2025 period. The research uses the Systematic Literature Review (SLR) method using scientific articles obtained from Google Scholar, Scopus, SINTA, and ScienceDirect databases. After applying the inclusion and exclusion criteria, 25 relevant articles were selected and analyzed thematically. The findings show that the growth of e-commerce in Indonesia has increased significantly due to technological advances and the acceleration of digital transformation during the COVID-19 pandemic. Consumers are increasingly choosing online shopping because of its convenience, efficiency, and accessibility. Digital promotions, online reviews, free shipping, and electronic payment systems have become important factors influencing purchasing decisions. E-commerce also provides opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand market reach and increase competitiveness. However, some challenges remain, including cybersecurity threats, personal data protection issues, digital literacy gaps, and the need for adaptive regulation. The study concludes that e-commerce plays a strategic role in shaping modern consumption patterns and supporting Indonesia's digital economy. Therefore, collaboration between governments, businesses, and society is essential to ensure the sustainable and inclusive development of e-commerce.